An LED-based visible light communication system for multicast - Jong-Sung Lee; Dae-Hee Lee; Sung-Jin Kim; Chang-Heon Oh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Visible Light Communication is a communication method that transmits data through light by pulsing an LED at high speed, performing broadcast communication for all devices existing in its coverage. Broadcast-based Visible Light Communication is limited to application to Internet of Things services, where various applications exist, although all receivers can communicate within the range of light sources. Therefore, this paper proposes an LED based Visible Light Communication system for multicast. The proposed system performs individual multicast by participating in communication only with receivers configured to use a specified ID value input at the transmitting side during data transmission. Experimental results show that the receiver can receive files individually according to a specified ID value.